Testing single aliquot regenerative dose (SAR) protocols for violet stimulated luminescence. (15th December 2018) - Colarossi, Debra; Chapot, Melissa S.; Duller, Geoff A.T.; Roberts, Helen M.
Abstract: Basic assumptions of the single aliquot regenerative dose (SAR) protocol are tested using the violet stimulated luminescence (VSL) signal from quartz. The VSL signal is shown to be reduced to a sufficiently low background level between SAR steps, and the SAR protocol appears to adequately correct for sensitivity changes during measurement. The VSL SAR protocol can recover a large (405 Gy) laboratory beta dose within uncertainties, however the mean value for the dose recovery ratio is commonly 0.8 or less. This poor behaviour is echoed in the measurements of equivalent dose (De ) for a sample with an expected De of ∼354 Gy, which underestimates De by 50–70%. Further investigations are required to understand the mechanisms underlying these underestimations in VSL SAR De values. Highlights: Compared two single aliquot regenerative dose protocols for VSL signal. Protocols assessed to minimise recuperation and optimise signal depletion. Partial success in dose recovery of ∼400 Gy using post-blue VSL signal. VSL signal gives 50–79% underestimation of the expected De.